Mesoscopic Structural States in Plastically Deformed Nanostructured Metal Materials; Physical Mesomechanics; Vol. 21, iss. 5 - Panin V. E. Viktor Evgenyevich; Surikova N. S. Nataljya Sergeevna; Smirnova N. S. Anastasiya Sergeevna; Pochivalov Y. I. Yury Ivanovich (2018, 2018)
Title screen